(3JaSjQ ShQI GdYfcHhJs - (3eLghds ((3YKeGf Hf hdjs)
(3ChdgG (B:s
(3HYO GdHSedI ; ShQI GdYfcHhJ ecjI bjd aj fGS ef CUMGH GdfHj Udi Gddg Ydjg hSde bO LRYhG ef GdeTcQjf cYeGQ hjGSQ hUgjH hcGfhG jYPHhfs
(3BNQgG (B:s
(3gh GdOjf Gdbje GdeSJbje hdcf CcKQ GdfGS dG jYdehf Pdc bhdg efjHjf Edjg Cj efUQajf Edi Gddgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs